Hydrogen activation on Pt-Sn nanoalloys supported on mixed Sn-Ce oxide films - Neitzel, Armin; Lykhach, Yaroslava; Skala, Tomas; Tsud, Nataliya; Johanek, Viktor; Vorokhta, Mykhailo; Prince, Kevin C.; Matolin, Vladimir; Libuda, Jörg (Physical Chemistry Chemical Physics, 2014)
We have studied the interaction of H-2 with Pt-Sn nanoalloys supported on Sn-Ce mixed oxide films of different composition by means of synchrotron radiation photoelectron spectroscopy and resonant photoemission spectroscopy. The model catalysts are prepared in a three step procedure that involves (i) the preparation of well-ordered CeO2(111) films on Cu(111) followed by subsequent physical vapor deposition of (ii) metallic Sn and (iii) metallic Pt. The formation of mixed Sn-Ce oxide is accompanied by partial reduction of Ce4+ cations to Ce3+. Pt deposition leads to the formation of Pt-Sn nanoalloys accompanied by the partial re-oxidation of Ce3+ to Ce4+. Subsequent annealing promotes further Pt-Sn alloy formation at expense of the Sn content in the Sn-Ce mixed oxide. Adsorption of H-2 on Pt-Sn/Sn-Ce-O at 150 K followed by stepwise annealing results in reversible reduction of Ce cations caused by spillover of dissociated hydrogen between 150 and 300 K. Above 500 K, annealing of Pt-Sn/Sn-Ce-O in a hydrogen atmosphere results in irreversible reduction of Ce cations. This reduction is caused by the reaction of hydrogen with oxygen provided by the mixed oxide substrate via the reverse spillover to Pt-Sn nanoalloy. The extent of the hydrogen and oxygen spillover strongly depends on the amount of Sn in the Sn-Ce mixed-oxide. We observe an enhancement of hydrogen spillover on Pt-Sn/Sn-Ce-O at low Sn concentration as compared to Sn-free Pt/CeO2. Although the extent of hydrogen spillover on Pt-Sn/Sn-Ce-O with high Sn concentration is comparable to Pt/CeO2, the reverse oxygen spillover is substantially suppressed on these samples.